DEVELOPING CREATIVE THINKING IN ART LESSONS: INTERNATIONAL PRACTICES AND LOCAL APPROACHES - Ergasheva Dilnoza Raximjonovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores strategies for developing creative thinking in art lessons, analyzing international practices and local approaches in Uzbekistan. The study examines pedagogical methods, curriculum designs, and classroom activities that enhance students’ creative potential. International experiences from countries such as Finland, the United States, Germany, and South Korea are highlighted, showcasing innovative approaches to foster creativity. The article also discusses the adaptation of these practices to the local context, emphasizing culturally relevant methods and the integration of national artistic traditions. Findings indicate that combining global best practices with local approaches can significantly enhance students’ creative thinking skills and overall artistic competence.